METODE KRITIK MATAN HADIS MUHAMMAD SYAHRUR - Juriono, Juriono (SHAHIH (Jurnal Ilmu Kewahyuan), 2020)
Recent research in the field of hadith has received more attention, both in terms of sanad and observations. Various methods are applied in an effort to understand the hadith from a different perspective. Some are still in the corridor of reasonableness, but some are too far. Like Muhammad Syahrur, who threw his methods and thoughts into observational criticism which led to pros and cons. There are those who agree and some who deny it. Educational background also affects a person's point of view. In this paper, we will discuss how Muhammad Syahrur's method is in criticizing the hadith observations. His biography and educational background were also in the spotlight. A number of figures who influenced his thinking will also be discussed in this paper. With the inductive method, the percentage of the pro and contra figures will be the conclusions in this study.